Digital archiving using AES-256 encryption and role-based access control to strengthen data security at Pusdatin - Muhammad Naufal Arits Fikri; Nisrina Labiba Sarwoko; Sembada Denrineksa Bimorogo; Nadiza Lediwara; Aulia Khamas Heikhmakhtiar (Institute of Computer Science (IOCS), 2026)
The rapid development of digital technology requires organizations, particularly government agencies, to implement robust and reliable data security systems. Data security is critical as the information managed is not only operationally valuable but also strategic and sensitive. The Center for Data and Information (Pusdatin) of the Ministry of Defense of the Republic of Indonesia plays a key role in managing and safeguarding defense-related data used for strategic decision-making. Based on observations and interviews, the existing data security system is considered adequate; however, several technical weaknesses remain, particularly in file management mechanisms and unstructured user access controls, which may lead to risks of data leakage and misuse. Therefore, this study aims to enhance data and file security through the implementation of Advanced Encryption Standard (AES-256) encryption and Role-Based Access Control (RBAC). This research employs the Waterfall method for system development, including analysis, design, implementation, and testing stages. System evaluation is conducted using functional testing and access control validation to assess the effectiveness of the implemented security mechanisms. The results indicate that AES-256 successfully ensures data confidentiality and integrity, while RBAC effectively restricts user access according to predefined roles, thereby reducing unauthorized access risks. The proposed system demonstrates improved data security and management efficiency, supporting a secure, efficient, and sustainable defense information system at Pusdatin The rapid development of digital technology requires organizations, particularly government agencies, to implement robust and reliable data security systems. Data security is critical as the information managed is not only operationally valuable but also strategic and sensitive. The Center for Data and Information (Pusdatin) of the Ministry of Defense of the Republic of Indonesia plays a key role in managing and safeguarding defense-related data used for strategic decision-making. Based on observations and interviews, the existing data security system is considered adequate; however, several technical weaknesses remain, particularly in file management mechanisms and unstructured user access controls, which may lead to risks of data leakage and misuse. Therefore, this study aims to enhance data and file security through the implementation of Advanced Encryption Standard (AES-256) encryption and Role-Based Access Control (RBAC). This research employs the Waterfall method for system development, including analysis, design, implementation, and testing stages. System evaluation is conducted using functional testing and access control validation to assess the effectiveness of the implemented security mechanisms. The results indicate that AES-256 successfully ensures data confidentiality and integrity, while RBAC effectively restricts user access according to predefined roles, thereby reducing unauthorized access risks. The proposed system demonstrates improved data security and management efficiency, supporting a secure, efficient, and sustainable defense information system at Pusdatin